LEGAL PERSPECTIVE ON IMPLICATIONS OF THE 'WILLOW PROJECT' RATIFICATION - Dwi Puteri, Adinda Virzilia (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2023)
Climate change is a crucial issue that has been questioned year after year, with the entire spectrum of society and countries worldwide trying to find alternatives to combat climate change. In this research, a literature review of journals, articles, and other publications relevant to the topic raised in the study was conducted. The literature review method is used to collect and analyze information from previous research related to The Willow Project, a massive-scale oil drilling project in Alaska by ConocoPhillips that is very controversial. Based on research references, due to the impact it will have, it can cause climate change four times faster amid a critical world because it is experiencing global boiling. Of course, this project needs to be stopped, and the law is the only tool that can be used by utilizing the existence of international environmental law as referred to the principle of international environmental law that a country in using and exploiting natural resources must not harm other countries. Not a few NGOs have succeeded in mobilizing the masses to boycott the project and file a lawsuit so that The Willow Project can be stopped